Incorporating Quality Considerations in Merger Analysis: Why, What, When, and How?. (June 2018) - Golder, Peter N.; Mitra, Debanjan; Moorman, Christine
Mergers are common occurrences reshaping the competitive landscape in many industries. Traditionally, merger analysis has focused on the impact of the merger on price. However, price analysis ignores the other half of the value proposition for customers, namely, the quality of the product or service being offered. The authors argue that merger analysis must fully incorporate quality considerations in order to understand how customers will be affected by the merger. Some mergers will promote quality, while other mergers will inhibit quality depending on a wide variety of product, market, and customer characteristics. In order to guide merger analysts in incorporating quality considerations, the authors provide a detailed framework for answering why, what, when, and how quality should be considered in merger analysis.